Acute Management Of Appendicitis Patients: Case Study - Heni Kusumawati (Jurnal EduHealth, 2023)
Appendicitis is infection bacteria, and the cause is a blockage in the lumen of the appendix such as lymphatic tissue hyperplasia, fekalit, and askaris worms and the presence of erosion of the appendix mucosa due to parasites such as E histolytica. At the same time, the signs and symptoms are dull pain in the epigastric area around the umbilicus and shifting to the lower right quadrant at Mc Burney's point, nausea, vomiting, decreased appetite, constipation, and fever. This scientific paper examines the relationship between acute pain and Appendicitis through nursing care. The research design used was a case study that explored the problem of nursing care for patients with Appendicitis with acute pain at Dr. Adjidarmo, Rangkasbitung, for three days with Mr. I. Data collection can be done through interviews, observation, physical examination, and documentation. The study results were that the patient complained of difficulty having bowel movements and lower right abdominal pain, like being stabbed with a pain scale of 7 (0-10) intermittent, and lack of appetite and could only finish ¼ portion of food. Body temperature 37.8 ° C, weight 40 kg, height 155 cm, BMI = 17 with low body weight interpretation, laboratory results of leukocytes 11.463 / Ul. Problems that arise are acute pain, hyperthermia, nutritional deficits, and constipation. The implementation reduces pain, lowers the temperature, improves nutritional status, and increases high-fiber foods, in addition to collaborating with the medical team in administering antibiotics, anti-pain, antipyretic, and anti-nausea therapy, as well as collaborating with the Nutrition team in administering a high-fiber diet. Nursing problems can be resolved on the third day with the criteria for decreased pain results with a pain scale of 2 (0-10), no fever with a temperature range of 36 °C - 37 °C and the results of the Leukocyte laboratory examination become 9.670 /Ul, increased appetite so that spend one portion of food and no constipation occurs.